El entorno familiar y su influencia en el desarrollo socio-afectivo de los niños y niñas del primer grado de educación básica de la escuela “Eloy Alfaro”, de la parroquia Alamor, cantón Puyango, provincia de Loja periodo lectivo 2013 – 2014”. lineamientos propositivos - GRANDA GRANDA, ESTEFANÍA ANGÉLICA (2015)
This thesis refers to "FAMILY ENVIRONMENT AND ITS IMPACT ON SOCIO -EMOTIONAL FOR CHILDREN FIRST GRADE BASIC EDUCATION SCHOOL"ELOYALFARO" PARISH ALAMOR CANTON PUYANGO LOJA PROVINCE. LECTIVO PERIOD 2013 - 2014". GUIDELINES PROACTIVE. The central issue raised in the present research work was: How family background affects the socio- emotional development of children in the first grade of elementary school education "Eloy Alfaro" the Alamor Parish, Canton Puyango, Loja Province, academic period 2013 - 2014? For processing the next General Purpose arose: To determine how the environment influences the Family Development Partner - Affective children of First Grade Basic Education Tax School "Eloy Alfaro" the Alamor Parish, Canton Puyango, Province of Loja. Teaching period 2013-2014. The methods used in the preparation of this research work were: Scientist, Inductive, Deductive, Descriptive and Statistical Model, which allowed for the discussion and comparison of the proposed variables. Survey applied to parents: Two instruments were applied. Teaching period 2013 - 2014 to establish their Family and Ebbe Test León Gross, applied to parents to determine Partner Affective development of their children. The methods used in the preparation of this research work were: Scientist, Inductive, Deductive, Descriptive and Statistical Model, which allowed for the discussion and comparison of the proposed variables. Survey applied to parents of children in the first grade of Basic Education Tax "Eloy Alfaro" School of Alamor Parish, Canton Puyango, Loja Province: Two instruments were applied. Teaching period 2013 - 2014 to establish their Family Environment and Ebbe Test León Gross, applied to parents to determine Partner Affective development of their children. After analyzing the survey data applied to parents to set the Family Environment of children, we reach the following conclusion: 48% of parents surveyed report that family practice love as part of their Family environment, 12% manifest Participatory Authority, 10% service Intent, 14% Positive treatment, and 16% Time coexistence. 17% of parents surveyed indicate that in your family there is absence of one parent, 10% say they are physically assaulted, 10% said that there is no communication, 9% think that there is insulation between the members of his family; 9% say there sibling rivalry and 45% believe that none is given. According to the results of the application of test Ebee León Gross concluded that. 65% of children surveyed earned a Satisfactory Affective Development Partner, 26% of children surveyed earned a Very Satisfactory Affective development partner and 9% of children surveyed earned a Partner Affective development Unsatisfactory.